2022
DOI: 10.3390/ijms23052524
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Betulin and Its Derivatives EB5 and ECH147 on the Antioxidant Status of Human Renal Proximal Tubule Epithelial Cells

Abstract: Betulin and its derivatives, 28-propyne derivative EB5 and 29-diethyl phosphonate analog ECH147, are promising compounds in anti-tumor activity studies. However, their effect on kidney cells has not yet been studied. The study aimed to determine whether betulin and its derivatives—EB5 and ECH147—influence the viability and oxidative status of human renal proximal tubule epithelial cells (RPTECs). The total antioxidant capacity of cells (TEAC), lipid peroxidation product malondialdehyde (MDA) level, and activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…In line with the results of Kruszniewska et al's research [15], we selected the compounds EB5, ECH147, betulin, cisplatin (Sigma-Aldrich, St Louis, MO, USA) and 5-fluorouracil (Sigma-Aldrich, St Louis, MO, USA) at concentrations of 0.1 and 0.5 µg/mL. For the cell treatment, the tested compounds were dissolved in DMSO (Merck, Darmstadt, Germany) and the mixture thus obtained was added to the culture media.…”
Section: Cell Culture Conditions and Treatmentsupporting
confidence: 90%
See 2 more Smart Citations
“…In line with the results of Kruszniewska et al's research [15], we selected the compounds EB5, ECH147, betulin, cisplatin (Sigma-Aldrich, St Louis, MO, USA) and 5-fluorouracil (Sigma-Aldrich, St Louis, MO, USA) at concentrations of 0.1 and 0.5 µg/mL. For the cell treatment, the tested compounds were dissolved in DMSO (Merck, Darmstadt, Germany) and the mixture thus obtained was added to the culture media.…”
Section: Cell Culture Conditions and Treatmentsupporting
confidence: 90%
“…Zehra et al reported the low cytotoxicity of betulin in mouse fibroblasts [49], whereas Małaczewska et al proved that it is highly toxic to these cells [50]. Kruszniewska et al confirmed that betulin and its derivatives EB5 and ECH147 are cytotoxic to RPTECs, except at lower concentrations such as 0.1 and 0.5 µg/mL [15]; therefore, they were chosen for this research.…”
Section: Importance Of Nephrotoxicity Studies and The Use Of Selected...mentioning
confidence: 99%
See 1 more Smart Citation
“…6). The presence of free for substitution groups in other positions open up opportunities for further modifications (Kruszniewska-Rajs et al, 2022). Drąg-Zalesińska et al (2019) have demonstrated significant activity of betulin-diamino butanoic ester 12 (Fig.…”
Section: Bioavailability Of the Terpenoidsmentioning
confidence: 99%
“…Additionally, the triterpenes have proven neuroprotective, hepatoprotective, antidiabetic, and antioxidant effects [ 25 , 26 , 27 ]. The major pharmacological properties of BE and its derivatives are summarized in Figure 2 .…”
Section: Properties and Molecular Mechanisms Of Betulin And Its Deriv...mentioning
confidence: 99%